Daily Methane Emission and Agronomic Data of Rice Cultivars in Latin America and the Caribbean for 2019 - soremi, paul; Chirinda, Ngonidzashe; Álvarez Vargas, Maria Fernanda; Graterol Matute, Eduardo Jose (2022)
This is the data collected for daily methane emission, root and yield attributes of four (4) rice cultivars under irrigated systems in Latin America and the Caribbean (LAC). The experiment was conducted at the International Center for Tropical Agriculture (CIAT), Palmira, Colombia in 2019; to determine which of the cultivars produce less methane without grain yield compromise. Data were collected to generate information on the role of the root and yield attributes towards methane mitigation strategy under irrigated system. The data is been processed for manuscript publication.